Relationships between soil physico-chemical properties and total viable bacterial counts in Sunderban mangrove forests, Bangladesh (Dhaka University Journal of Biological Sciences, 2012)
Although soil bacterial communities are one of the important biotic components that influence decomposition and nutrient mineralization in the terrestrial ecosystems, factors driving this biotic community in the Sunderban mangrove forests are not well studied. The present study examined the importance of soil physico?chemical properties in driving soil bacterial communities in the Sunderban mangrove forests, Bangladesh. Soils were collected from 12 locations under four sites, namely Koromjal, Kotka, Hironpoint, and Dublarchar of Sunderban forests. Results showed a large range of variation in total bacterial colony counts (7.65 × 104 ? 14.5 × 104 cfu/g soil), soil moisture (9.0 ? 27.0%), total nitrogen (0.057 ? 0.158%), available nitrogen (0.504 ? 2.016 ?g/g soil), soil salinity (20.99 ? 34.99 mg chloride/g soil), and organic carbon (0.460 ? 0.885%). Data of the present study revealed that the number of total viable bacterial count was significantly and positively correlated only with total nitrogen content in soil indicating that total nitrogen content is the major driving factor of bacterial communities in the Sunderban mangrove forest soils.DOI: http://dx.doi.org/10.3329/dujbs.v21i2.11515 Dhaka Univ. J. Biol. Sci. 21(2): 169-175, 2012 (July)